DIY : repair, renovate, and decorate with over 450 step-by-step projects - Cassell, Julian; Parham, Peter; Coleman, Theresa (New York, New York : DK Publishing, 2025)
"Whether you need to do a quick fix or a large DIY project, find out how to tackle any DIY task with confidence following this revised and updated step-by-step guide. From fitting a shower cubicle to applying different painting techniques, the simple, clear, unintimidating instructions ensure even hard jobs are made easy, whatever your level of ability. With step-by-step photographs of every technique and process, DIY breaks down every stage of every task, from choosing tools and essential safety guidance to advice for tackling big jobs and fixing common problems. Including the latest home features like boiling-water taps and smart security systems, up-to-date safety guidelines, and eco-conscious solutions from paint choices to solar panels, this is the tried-and-trusted guide that no homeowner should be without."--Provided by publisher.
Includes index.
Keywords: Dwellings -- Maintenance and repair; Dwellings -- Remodeling; Do-it-yourself work; Handbooks and manuals